2009
DOI: 10.1029/2007jb005326
|View full text |Cite
|
Sign up to set email alerts
|

Lithospheric geometry of the Wopmay orogen from a Slave craton to Bear Province magnetotelluric transect

Abstract: [1] Two-dimensional inversions of lithospheric-probing magnetotelluric (MT) data at a total of 20 sites acquired along an approximately east-west 300-km-long profile across the Wopmay orogen in the Northwest Territories, Canada, provide electrical resistivity models of the boundary between the Archean Slave craton and the adjacent Proterozoic Bear Province. An analysis of distortion effects and structural dimensionality indicates that the MT responses are primarily one-dimensional or only weakly two-dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 102 publications
1
41
0
1
Order By: Relevance
“…These include deep-seismic reflection profiling (Cook et al, 1999;Cook and Erdmer, 2005;Oueity and Clowes, 2010), magnetotelluric experiments (Wu et al, 2005;Spratt et al, 2009), and teleseismic data acquisition (Bostock, 1998;Mercier et al, 2008;Snyder et al, 2014). The 2D geophysical data in those studies collectively support that there is a stacked east-dipping lithospheric mantle beneath this region, related to subducted and frozen oceanic crust (e.g., Cook et al, 1999).…”
Section: Geophysicsmentioning
confidence: 95%
“…These include deep-seismic reflection profiling (Cook et al, 1999;Cook and Erdmer, 2005;Oueity and Clowes, 2010), magnetotelluric experiments (Wu et al, 2005;Spratt et al, 2009), and teleseismic data acquisition (Bostock, 1998;Mercier et al, 2008;Snyder et al, 2014). The 2D geophysical data in those studies collectively support that there is a stacked east-dipping lithospheric mantle beneath this region, related to subducted and frozen oceanic crust (e.g., Cook et al, 1999).…”
Section: Geophysicsmentioning
confidence: 95%
“…Geophysical studies have shown that the Hottah terrane and Great Bear magmatic zone have properties distinct from those of the Slave craton and overlying Coronation margin to the east, and the Fort Simpson magnetic high and enigmatic Nahanni terrane to the west ( Fig. 1; Fraser et al 1972;Hoffman 1988a;Cook et al 1999;Aspler et al 2003;Cook and Erdmer 2005;Wu et al 2005;Spratt et al 2009;Oueity and Clowes 2010;Ootes et al 2013;Hayward and Corriveau 2014). Much of what has been "imaged" in these experiments is covered by the Phanerozoic platform, and directly assessing the underlying bedrock components, especially of the Hottah terrane, is not currently possible.…”
Section: Geological Settingmentioning
confidence: 99%
“…The Wopmay fault zone is a north-south-striking crustal-scale fault that delimits the western extent of exposed Archean rocks in the Wopmay Orogen (Figs. 1, 2;St-Onge et al 1983;King 1986;Bowring and Podosek 1989;Housh et al 1989;Jackson 2008;Jackson et al 2006Jackson et al , 2013Spratt et al 2009;Jackson and Ootes 2012: also called medial zone by Hildebrand et al 1991Hildebrand et al , 2010a. West of Wopmay fault zone are the remnants of the >1.9 Ga Hottah terrane, which was extensively overprinted by ca.…”
Section: Geological Settingmentioning
confidence: 99%
“…Variations in the lithospheric mantle may hold clues to metal enrichment in overlying geological provinces (Spratt et al 2009) and also provide information for geodynamic interpretations of the overlying crust. MT data is likely to become increasingly important as more geologists and explorers become interested in the deep earth.…”
Section: Magnetotelluric Surveysmentioning
confidence: 99%